Influence of the structure of sub‐micrometer core‐shell rubber particles and matrix composition on the mechanical properties, morphological structure and deformation mechanism of rubber‐modified polyphenylene oxide/polystyrene blends. Issue 42 (15th August 2022) - Song, Lixin; Zhang, Qian; Hao, Yongsheng; Cong, Fei; Chi, Weihan; Li, Yongchao; Liu, Zhe; Shi, Ying
Abstract: A series of polybutadiene‐graft‐polystyrene (PB‐g‐PS) graft copolymers with different core–shell ratios (PB/PS) are synthesized using emulsion polymerization. Subsequently, the PB‐g‐PS graft copolymers are blended with polyphenylene oxide (PPO) and polystyrene (PS) to prepare PPO/PS/PB‐g‐PS blends with varying compositions. The effects of the core–shell ratio of PB‐g‐PS graft copolymer and matrix composition on the mechanical properties, micromorphology, and deformation mechanism of the blends are investigated. The results show that the synthesized PB‐g‐PS graft copolymer has extremely high toughening efficiency. The blends with high toughness and excellent processability can be prepared by introducing it and PS into PPO at the same time, and then obtain better end‐use properties and broaden the applications. With the increase of the core‐shell ratio of PB‐g‐PS graft copolymer, the rubber particles gradually gather in the matrix. With an increase of PPO content in the matrix, the rubber particles gradually become uniformly dispersed, the impact strength and yield strength of the blends gradually increase, the coarseness of the impact fracture surface of the blends gradually increase, and massive elongated cavities appear. The blends undergo a brittle ductile transition, and its deformation mechanism change from the initial cracking to shear yielding. Abstract : PB‐g‐PS graft copolymer with core‐shell structure was prepared by emulsion polymerization. The matrix toughness was provided by the core phase (PB), while the shell phase (PS) has good compatibility with PPO, which ensured that the core‐shell particles of PB‐g‐PS can be uniformly dispersed in the PPO/PS matrix. It is found that the impact toughness of PPO/PS blends can be effectively improved by controlling the core‐shell ratio of PB‐g‐PS graft copolymer.